Reinforced concrete beams with lightweight concrete infill - Vimonsatit, Vanissorn; Wahyuni, Ade; Nikraz, Hamid (Academic Journals, 2012)
In structural design, an ideal situation in material saving is to reduce the weight of the structure without having to compromise on its strength and serviceability. A new lightweight sandwich reinforced concrete section has been developed with a novel use of lightweight concrete as infill material. The section, namely LSRC section, is suitable for use as beam or slab members. Experimental investigations into the strength of beams with LSRC section shows promising results under both flexural and shear tests. Based on the test results, the flexural capacity of LSRC beams was found to be almost identical to the capacity of the equivalent solid beam. The shear capacity of the LSRC beams was expectedly reduced due to the low compressive strength of the lightweight concrete infill material. ANSYS 12.1 was employed to develop three dimensional nonlinear finite element models of LSRC beams and was verified against the experimental results.